Mem internetowy jako gatunek medialny. Historia, środki wyrazu i funkcja w kulturze - Magdalena Kamińska (Napis)
The internet meme, defined by users most simply as a ‘funny picture off the internet’, is a fascinating, albeit long-ignored by academia, phenomenon of contemporary culture. The article formulates a definition of this phenomenon and describes its origins. In outlining its characteristics, the text emphasises especially those interpretations that include memes in the wide category of contemporary folklore. At the same time, the article defines memes as texts originating in an organic way, and contributing to the creation of a community of identity, on the grounds of a culture of participation. The study also presents a short analysis of stylistic devices utilised by creators of memes, complete with examples, and a critical discussion of the attempts at a utilitarian application of this media genre.